OPTIMIZATION PITCH AND CLEARANCE FOR DOUBLE HELICAL RIBBON AGITATOR IN BRIQUETTE DOUGH MIXING MACHINE: ANALYSIS OF TORQUE AND POWER IMPACT - Ma'a, Mustaza; Faadhilah, Hanif; Wijianto, Agus; Novison, Roni (Jurnal Rekayasa Mesin, 2025)
Briquette dough kneading machines have become an integral part of the briquette production process in industry. This study aims to analyze the effect of pitch (distance between two windings) and clearance (distance between stirrer and machine wall) on the performance of double helical ribbon stirrer in stirring briquette dough. The numerical method used is Discrete Element Method (DEM), using a stirring speed of 50 rpm and a particle size of 10 mm. In this simulation, the briquette mixture was modeled as two granular materials consisting of spherical particles. The particles were characterized using density, with briquette powder at 766 kg/m3 and starch glue at 1000 kg/m3. Simulation results show that variations in pitch and clearance significantly affect the distribution of torque, mechanical power, and dough flow. The stirrer with 157.5 mm pitch has the smallest torque and power, then the torque and mechanical power increase about 260% in the stirrer with 118.5 mm pitch. Then the stirrer with a pitch of 94.8 mm has a very high torque and mechanical power with an increase over the previous stirrer of about 1500%. The researcher concluded that the double helical ribbon stirrer with a pitch distance of 118.5 mm and a clearance of 10 mm is the appropriate stirrer to be used, with torque and power of 41.62749 Nm and 318.3174 W. This is corroborated by the simulation results with a visual assessment showing that the shear force and homogeneity are in optimal condition, although the torque and power are not too close to the design calculation results of 53.0836 Nm and 277.8042 W.